2019
DOI: 10.2478/afpuc-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal electrophysiological responses and changes in oxidative stress marker and serum lipid profile to pharmacological and non-pharmacological treatments of high-fat-fructose diet induced metabolic syndrome

Abstract: The aim of our study was to evaluate the possibility of influencing the risk factors of metabolic syndrome (MetS) and metabolic cognitive syndrome. As a model of MetS, we used high-fat-fructose diet (HFFD) fed hypertriacylglycerolemic (HTG) rats. Control group included HTG rats fed with HFFD during 8 weeks (HFFD8). Furthermore, we tested the effect of pharmacological and non-pharmacological therapies. Non-pharmacological therapy, which we chose, was a change in diet from HFFD (5 weeks) to standard one (3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The aim of the present study was to evaluate effects of diet improvement and/or RA administration on metabolic as well as on functional vascular and hippocampal changes induced by a high-fat-fructose diet (HFFD) in rats. We were motivated by our previous findings of the RA effect in MetS-like conditions (18) where we studied the effect of energy restriction in combination with RA on plasma lipids in rats fed HFFD. The results showed that changing the HFFD diet to the standard induced a drop of total cholesterol to almost initial levels.…”
mentioning
confidence: 99%
“…The aim of the present study was to evaluate effects of diet improvement and/or RA administration on metabolic as well as on functional vascular and hippocampal changes induced by a high-fat-fructose diet (HFFD) in rats. We were motivated by our previous findings of the RA effect in MetS-like conditions (18) where we studied the effect of energy restriction in combination with RA on plasma lipids in rats fed HFFD. The results showed that changing the HFFD diet to the standard induced a drop of total cholesterol to almost initial levels.…”
mentioning
confidence: 99%